Orthodontic Considerations for Traumatized Teeth: An Overview - Karishma Rathore1, Debasruti Naik2, Stithaprajna Lenka3, Ramesh Nagarajappa4, Utkalika Das1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
This article reviews the orthodontic consideration for the proper management of traumatic dental injurieswhich requires an understanding of the immediate and short- term response to the involved tissues: theperiodontal ligament (PDL), pulp, and alveolar bone. This document discusses a few protocols required fororthodontic management of traumatically injured teeth.